Nanoporous azo polymers (NAPs) for selective CO2 uptake. (December 2018) - Bera, Ranajit; Ansari, Mosim; Alam, Akhtar; Das, Neeladri
Graphical abstract: Highlights: Facile synthesis of nanoporous azo polymers (NAPs ) using metal-catalyst free polycondensations in basic medium. NAPs have been designed to include triptycene, phorphyrin and azo units in the polymer backbone. NAPs exhibits high surface area up to 1095 m 2 g −1 . High CO2 uptake up to 3.93 mmol g −1 at 273 K and 1 bar uptake by theseNAPs . Good CO2 /N2 selectivity (up to 64 at 273 K) shown by theseNAPs. Abstract: Two nanoporous azo polymers (NAPs ) have been designed incorporating triptycene and porphyrin motifs in the polymer framework that are linked covalently by azo functional groups.NAPs are synthesized using metal-catalyst free polycondensations in basic medium. These are thermally stable, microporous (Type-I isotherms in N2 adsorption–desorption measurements at 77 K) and have moderately high surface areas (SABET = 1095 and 923 m 2 g −1 ).NAPs show enhanced surface areas relative to either triptycene networks with azo-linkages or porphyrinic polymers having azo bridges.NAPs register high CO2 uptake (upto 3.93 mmol g −1 at 1 bar and 273 K) with good CO2 /N2 selectivity (upto 64:1 at 273 K) for CO2 capture from flue gas. Incorporation of CO2 -philic porphyrin rings and N2 -phobic azo groups results in improved CO2 /N2 selectivity in these triptycene based microporous polymers. Performance ofNAPs as nanoporous polymer (in terms of gas sorption properties such as surface areas, low pressure gas uptake and gas selectivity) is also better than several non-triptycene/porphyrin but azo based porous organic polymers (POPs).NAPs have potential use in post-combustion CO2 capture and sequestration technology.